2005
DOI: 10.2116/analsci.21.403
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrollable Cation Extraction with Crowned Oligo(spirobenzopyran)s

Abstract: Since light is one of the most effective and energy-saving means for changing molecular functions, extensive studies about photoresponsive reagents bearing a photochromic moiety have been reported so far. [1][2][3][4] Spirobenzopyrans, typical photochromic compounds, isomerize from their electrically neutral spirobenzopyran forms to the corresponding zwitterionic merocyanine form, which has a maximum absorption wavelength around 550 nm, by UV-light irradiation, and vice versa by visible-light irradiation and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…If we consider the photoisomerization process, the nonpolar BSP molecule when irradiated with UV light isomerizes into a highly polar zwitterionic system MC, and it is known that this system can be used to transport metal ions across organic-aqueous barriers with UV light. [40][41][42] However, it has recently been proposed that ILs are structured at the microand nanoscopic levels, containing polar and non-polar domains. 22,23,43 This hypothesis could explain the reason we observe such low values of K e ; potentially at equilibrium the BSP isomer resides in the non-polar domain of the IL.…”
Section: Thermochromic Propertiesmentioning
confidence: 99%
“…If we consider the photoisomerization process, the nonpolar BSP molecule when irradiated with UV light isomerizes into a highly polar zwitterionic system MC, and it is known that this system can be used to transport metal ions across organic-aqueous barriers with UV light. [40][41][42] However, it has recently been proposed that ILs are structured at the microand nanoscopic levels, containing polar and non-polar domains. 22,23,43 This hypothesis could explain the reason we observe such low values of K e ; potentially at equilibrium the BSP isomer resides in the non-polar domain of the IL.…”
Section: Thermochromic Propertiesmentioning
confidence: 99%
“…38 The photoinduced changes in the metal-ion extractability of crown ether derivatives bearing three or four spirobenzopyran moieties (10 or 11) and their analogues were studied using 1,2-dichloroethane as an organic solvent. 17 Under dark conditions, these compounds extracted Cu 2+ , Ag + , and Pb 2+ with their counteranions from the aqueous phase to the organic phase. The extraction equilibrium constants of the photochromic crown ether derivatives for Cu 2+ and Ag + were successfully determined.…”
Section: ·2 Extraction-spectrophotometric Flow Injection Analysismentioning
confidence: 98%
“…The tunable selectivity by photoirradiation is interesting from the viewpoint of photocontrollable analysis and application. 9,10 In addition, we had reported that the ISEs based on the similar liquid-crystalline membranes without any azobenzene derivative were applied successfully to K + assays in blood sera. 4 Therefore, the ISEs based on the liquid-crystalline membranes containing azobenzene derivative 2 are also useful for K + assays in real biological samples, because the sensitivity and selectivity for K + are comparable to or higher than those for K + -ISEs reported previously.…”
mentioning
confidence: 99%